2022
DOI: 10.1021/acsestwater.2c00358
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Impacts of Disposable Face Masks and Gloves on Freshwater Benthic Fauna and Sediment Biogeochemistry

Abstract: To reduce virus transmission, the use of personal protective equipment (PPE) increased substantially during the COVID-19 global pandemic. As a result, disposable face masks and gloves made from plastic polymers rapidly entered the environment, with little understanding of ecological impacts. Many plastic polymers sink to the bottom of freshwater bodies, either immediately or following biofouling and degradation, posing a potential risk to the benthos. We assessed the acute and chronic ecotoxicity of disposable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
0
1
0
Order By: Relevance
“…However, we also observed worms entangled in fibers, suggesting a strong direct interaction. Toxicity was not directly measured here; however, in other work, we observed both physical and chemical impacts of plastic on similar benthic species [111]. Here, we observed worms as a significant potential driver of the effects observed in PET microcosms (Figure 2).…”
Section: Pet Impacts Ecosystem Metabolismsupporting
confidence: 63%
“…However, we also observed worms entangled in fibers, suggesting a strong direct interaction. Toxicity was not directly measured here; however, in other work, we observed both physical and chemical impacts of plastic on similar benthic species [111]. Here, we observed worms as a significant potential driver of the effects observed in PET microcosms (Figure 2).…”
Section: Pet Impacts Ecosystem Metabolismsupporting
confidence: 63%
“…One study reported that chronic exposure to the particles alone significantly impacted reproduction in Tigriopus japonicus 15 while another study showed that exposure to degraded face masks may impact genes associated with reproduction in Danio rerio . Using Lumbriculus variegatus , Chomiak et al 16 showed that chemicals and particles released from face masks may impact their short-term behaviour and long-term population, respectively. Nonetheless, there is not sufficient data available yet to fully understand the ecological impacts of face mask pollution on aquatic invertebrates.…”
Section: Introductionmentioning
confidence: 99%